Effect of biochar amendment on metal mobility, phytotoxicity, soil enzymes, and metal-uptakes by wheat (Triticum aestivum) in contaminated soils. (November 2022) - Pandey, Bhawna; Suthar, Surindra; Chand, Naveen
Abstract: The use of low-cost substances such as biochar could be a sustainable approach to reduce the mobility, accumulation, and toxic impact of heavy metals in crop systems. This study investigates the effect of biochar amendment on heavy metal (Cr, Cd, Cu, Pb, Ni, Zn, Mg and Fe) mobility, bioaccumulation factor (BAF), plant (wheat) metal-uptake, plant oxidative stress, and soil enzymatic profile in contaminated industrial soil. Biochar was obtained from slow pyrolysis of Lantana (LBC), and Parthenium (PBC) biomass, and applied at 3% rates in contaminated soils for wheat crop study under a greenhouse experimental setup. Results show in comparison with control setups, low mobility of Cr (14.15–16.35%), Cd (7.17–15.24%), Cu (9.81–12.97%), Pb (7.99–15.23%), Ni (1.52–2.38%), Zn (10.47–14.42%), Mg (48.85–52.89%), and Fe (19.13–19.90%) contents in soils. The heavy metal uptake rates were 63.08% (Cr), 78.07% (Cd), 74.61% (Cu), 78.11% (Pb), 75.73% (Ni), 69.71% (Zn), 28.78% (Mg), and 49.26% (Fe) lower in biochar amendments, compared with the control treatments. Similarly, the biochar amended treatments exhibited low oxidative stress in wheat plants than control setups. In addition, soil enzymes (dehydrogenase, β-glucosidase, alkaline phosphatase, and urease) alleviated in biochar amended soils indicating reduced toxicity of metals in experimental soils. In summary, this study indicates that biochar amendment in contaminated soils not only improves plant growth but also lowers the rates of soil and plant toxicity and metal bioavailability as well. Graphical abstract: Image 1 Highlights: The impact of the biochar (BC) amendment on metal mobility is investigated. Wheat crops show low metal bioaccumulation in BC amended setups. BC amendment causes low oxidative stress by heavy metals in the plant.